Комп’ютерне моделювання режиму переривистих струмів електроприводу постійного струму з трифазним керованим випрямлячем - Ковальова, Юлія Вікторівна (НТУ "ХПІ", 2018)
Режим переривистого струму вентильних електроприводів постійного струму з’являється в інтервалах неробочого ходу механізмів. Розрахунок ємності конденсаторів фільтру виконується через діюче значення змінної складової випрямленої напруги і тому виникає завдання розробки аналітичної методики для її розрахунку через коефіцієнт пульсацій напруги з урахуванням кута керування, електромагнітної сталої часу якоря і струму навантаження. Вираз для розрахунку коефіцієнта пульсацій напруги з урахуванням впливаючих факторів, отриманий методом планування експерименту на основі комп'ютерного моделювання в програмному пакеті Simulink, дозволяє визначити ємність конденсаторів фільтрів і підвищити ефективність електромеханічного перетворення електроенергії за рахунок знижен-ня змінної складовою випрямленої напруги.

The mode of intermittent current for DC motor with three-phase thyristor rectifier appears in the idle intervals of some mechanisms. Active andpassive filters reduce the variable component of the rectified voltage. The capacitance of the capacitors filter is determined by the effective value of the variable component of the rectified voltage. Necessity of developing an analytical method for calculating the effective value of the variable component of the rectified voltage in the intermittent current mode, taking into account three parameters: the control angle, the electromagnetic time constant of the armature circuit and the load current. To determine the dependence of the effective value of the variable component of the rectified voltage for three parameters in theintermittent current mode. The effective value of the variable component of the rectified voltage is suggested to be determined through the voltage pulsations factoras the ratio of the effective value of the variable component of the rectified voltage to its constant component. The dependence of the pulsations factor from the parameters of the mode is determined using computer simulation of the mode for intermittent current. The computer model is developed in the software package Simulink, which allows to change each parameter of the mode separately while stabilizing the other two. Numerical dependences of the pulsation factor on each parameterare obtained. The analytical dependence of the voltage pulsations factor on three influencing values was obtained by the method of experiment planning. For the first time, method has been developed for calculating pulsation factor of the rectified voltage and calculating the effective value of the variable component in the mode of intermittent currents, taking into account three parameters. The proposed method will allow to rationally determine the capacity of the capacitors of active and passive filters and increase the efficiency of electromechanical power conversion by reducing the variable component of the rectified voltage.
Computer simulation of intermittent current mode of DC electric drive with three-phase controlled rectifier
Keywords: тиристорний випрямляч; пульсації напруги; кут керування; механізми; коефіцієнт пульсацій; thyristor rectifier; voltage pulsations